Paced Auditory Serial Addition Test (PASAT 3.0s): Demographically corrected norms for the Portuguese population - Sousa, C. S.; Neves, M. R.; Passos, A. M.; Ferreira, A.; Sá, M. J. (Applied Neuropsychology Adult, 2018)
The main goal of this study was to produce adjusted normative data for the Portuguese population on the Paced Auditory Serial Addition Test (PASAT 3.0s), the version used in the Brief Repeatable Battery of Neuropsychological Tests developed by the National Multiple Sclerosis Society. The study included 326 community-dwelling individuals (199 women and 127 men) aged between 20 and 70 (mean=40.33, SD=14.40), who had educational backgrounds ranging from 4 to 23 years of schooling (mean=12.28, SD=4.39). Age, gender and qualifications revealed differences in explaining their performance on the PASAT 3.0s. Men had significantly better performance on the PASAT 3.0s than women, even though this represents a small effect size r=0.18. Demographically corrected normative data was developed and important information regarding performance on the PASAT 3.0s test is provided. Results are discussed and presented in tables and a formula is presented for computing age, gender and education adjusted T-scores for performance on the PASAT 3.0s. These results should be considered as useful reference values for clinicians and investigators when applying the PASAT 3.0s to assess cognitive function like information processing speed in different pathologies.